Finite element modelling and analysis of the human cervical spine - Ng, Hong Wan (2008)
In this report, a non-linear three-dimensional multi-segmental finite element (FE) model of the intact cervical spine, including the associated ligamentous tissues was developed and validated in terms of the range of motions (ROMs), force/displacement responses, internal strains and disc pressure under a wide range of physiological loading conditions.